Translation Methods and Procedures in Bilingual Storybooks - Arif Hidayat; Danang Dwi Harmoko (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2018)
ABSTRACTThis research is aimed at finding the procedures and method of three bilingual storybooks. The research method used is descriptive qualitative with content analysis. Based on the theory of Newmark about translation method and procedures, it is found that the frequently used procedures are literal, modulation, shift, addition and reduction. The translation on the first book indicated that the translator uses shift modulation, couplet, cultural equivalent, addition. In the second book, the procedures used are literal, addition, modulation, reduction, transference, expansion and couplet. Whilst, in the third book, there couplet, literal, addition, reduction, modulation, cultural equivalent, shift, synonymy, expansion procedures are found. On the other hand, the most dominant procedure used is literal and the translation method used is semantic translation. The method shows the translation orientation of the translators.Keywords: Translation procedures, translation method, Newmark, bilingual storybooks